Platygaster opaca Ruthe 1859 ... - Awad, Jessica; Zimmermann, Dominique; Talamas, Elijah (Zenodo, 2024)
Platygaster opaca Ruthe, 1859 Platygaster opacus Ruthe, 1859: 313. Type locality: Iceland. Platygaster opaca – Dalla Torre 1898: 475 (emendation). Material examined Holotype ICELAND • 1 ♀; [Staudinger leg.]; NHMW-HYM#0009552. ... : Published as part of Awad, Jessica, Zimmermann, Dominique & Talamas, Elijah, 2024, A photographic type catalogue of Platygastroidea (Insecta, Hymenoptera) in the Natural History Museum Vienna, pp. 1-58 in European Journal of Taxonomy 938 on page 10, DOI: 10.5852/ejt.2024.938.2565, http://zenodo.org/record/12106502 ...